2022
DOI: 10.2105/ajph.2021.306541
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic and Age Differences in the Direct and Indirect Effects of the COVID-19 Pandemic on US Mortality

Abstract: Objectives. To estimate the direct and indirect effects of the COVID-19 pandemic on overall, race/ethnicity‒specific, and age-specific mortality in 2020 in the United States. Methods. Using surveillance data, we modeled expected mortality, compared it to observed mortality, and estimated the share of “excess” mortality that was indirectly attributable to the pandemic versus directly attributed to COVID-19. We present absolute risks and proportions of total pandemic-related mortality, stratified by race/ethnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…[13][14][15][16] Concerningly, other studies also reported excess out-of-hospital deaths during the early phases of the pandemic [17][18][19] and it is estimated that between one quarter and one half of the excess all-cause deaths in North America during 2020 did not have SARS-CoV-2 infection. [20][21][22][23][24] These patterns are particularly worrisome since inpatient and outpatient visit rates after the 2003 SARS-CoV-1 epidemic did not recover to preepidemic levels in affected cities until several years later. [25] Indeed, recent reports suggest that although outpatient visit rates have increased in the US since the almost 60% decline seen in the early weeks of the pandemic, they have still not recovered to pre-pandemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] Concerningly, other studies also reported excess out-of-hospital deaths during the early phases of the pandemic [17][18][19] and it is estimated that between one quarter and one half of the excess all-cause deaths in North America during 2020 did not have SARS-CoV-2 infection. [20][21][22][23][24] These patterns are particularly worrisome since inpatient and outpatient visit rates after the 2003 SARS-CoV-1 epidemic did not recover to preepidemic levels in affected cities until several years later. [25] Indeed, recent reports suggest that although outpatient visit rates have increased in the US since the almost 60% decline seen in the early weeks of the pandemic, they have still not recovered to pre-pandemic levels.…”
Section: Discussionmentioning
confidence: 99%
“…( Grier and Bryant, 2005 ) The COVID-19 pandemic continues to disproportionately burden populations who have been systematically and historically marginalized. ( Zalla et al, 2022 , Karmakar et al, 2021 ) While health communication interventions alone are insufficient to address inequity (and in fact, could reinforce inequity if access to information is more readily available to higher-resourced groups ( Viswanath et al, 2012 ), PSAs can be one component of an equity-centered response, by providing easy-to-understand information, to broad or targeted audiences, and to counter the spread of misinformation by conveying accurate information from trusted sources. ( Wakefield et al, 2010 , Viswanath et al, 2020 )…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of studies have focused on COVID-19 infection rates, hospitalisations and deaths, the true toll of the pandemic extends beyond the direct morbidity and mortality from SARS-CoV-2 infection. By January 2022, over 1 million excess deaths occurred in the USA alone; while COVID-19 was documented as a primary or underlying cause for 901 422 deaths, an estimated 11% of excess deaths were indirectly related to COVID-19 infection 1 2. Globally, 2.5 million excess deaths were directly and indirectly attributed to COVID-19 from January 2020 to June 2021 in Organisation of Economic Co-operation and Development countries, representing a 16% increase in the expected number of deaths 3.…”
Section: Introductionmentioning
confidence: 99%